Clarifying the nature of stochastic fluctuations and accumulation processes in spontaneous movements - Bogler, Carsten; Grujičić, Bojana; Haynes, John-Dylan (Frontiers in Psychology, 2023)
Experiments on choice-predictive brain signals have played an important role in the debate on free will. In a seminal study, Benjamin Libet and colleagues found that a negative-going EEG signal, the readiness potential (RP), can be observed over motor-related brain regions even hundreds of ms before the time of the conscious decision to move. If the early onset of the readiness potential is taken as an indicator of the "brain's decision to move" this could mean that this decision is made early, by unconscious brain activity, rather than later, at the time when the subject believes to have decided.However, an alternative kind of interpretation, involving ongoing stochastic fluctuations, has recently been brought to light. This stochastic decision model (SDM) takes its inspiration from leaky accumulator models of perceptual decision making. It suggests that the RP originates from an accumulation of ongoing stochastic fluctuations. In this view the decision happens only at a much later stage when an accumulated noisy signal (plus imperative) reaches a threshold. Here we clarify a number of confusions regarding both the evidence for the stochastic decision model as well as the interpretation that it offers. We will explore several points that we feel are in need of clarification: (a) the empirical evidence for the role of stochastic fluctuations is so far only indirect; (b) the interpretation of animal studies is unclear; (c) a model that is deterministic during the accumulation stage can explain the data in a similar way; (d) the primary focus in the literature has been on the role of random fluctuations whereas the deterministic aspects of the model have been largely ignored; (e) contrary to the original interpretation the deterministic component of the model is quantitatively the dominant input into the accumulator; and finally (f) there is confusion regarding the role of"imperative" in the SDM and its link to "evidence" in perceptual decision making. Our aim is not to rehabilitate the role of the RP in the free will debate. Rather we aim to address some confusions regarding the evidence for accumulators playing a role in these preparatory brain processes.